2016
DOI: 10.1016/j.lfs.2016.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin reduces effects of ET-1 and TLR2-mediated cerebrovascular hyperreactivity in diabetes

Abstract: Aims The anti-hyperglycemic agent linagliptin, a dipeptidyl peptidase-4 inhibitor, has been shown to reduce inflammation and improve endothelial cell function. In this study, we hypothesized that DPP-IV inhibition with linagliptin would improve impaired cerebral blood flow in diabetic rats through improved insulin-induced cerebrovascular relaxation and reversal of pathological cerebrovascular remodeling that subsequently leads to improvement of cognitive function. Main Methods Male type-2 diabetic Goto-Kakiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Linagliptin has been shown to improve cerebrovascular dysfunction observed in diabetes through anti-inflammatory and vasodilatory effects in a glucose-independent manner [32]. Alternatively, linagliptin may restore cerebrovascular function via the regulation of hyper-reactivity to endothelin 1 and Toll-like receptors 2 expression [33]. Treatment with sitagliptin was reported to reverse memory impairment in HFD-fed mice through reduced oxidative stress and enhanced neurogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Linagliptin has been shown to improve cerebrovascular dysfunction observed in diabetes through anti-inflammatory and vasodilatory effects in a glucose-independent manner [32]. Alternatively, linagliptin may restore cerebrovascular function via the regulation of hyper-reactivity to endothelin 1 and Toll-like receptors 2 expression [33]. Treatment with sitagliptin was reported to reverse memory impairment in HFD-fed mice through reduced oxidative stress and enhanced neurogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Linagliptin seems to exhibit antagonistic properties towards TLR-2s (Toll-like receptors 2) [23]. TLR-2s serve an essential role in modulating the immune response of the brain [66].…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
“…Intriguingly, dual blockade of both ET A and ET B receptors with bosentan improves the maximum relaxation response (Li et al 2011). A recent study demonstrated that oral hypoglycemic linagliptin improves the ET-1-mediated cerebrovascular dysfunction observed in the GK model through a reduction in ET-1 plasma levels and reduced cerebrovascular hyperreactivity (Hardigan et al 2016a, Hardigan et al 2016c. This effect is potentially a result of linagliptin causing a decrease in endothelial toll like receptor 2 (TLR2) expression and a subsequent increase in NO bioavailability (Hardigan et al 2016a, Hardigan et al 2016c.…”
Section: Agonist-induced Vasoreactivitymentioning
confidence: 99%